The expression of three members of the achaete-scute gene complex correlates with neuroblast segregation in Drosophila. - Cabrera, C.V.; Martinez Arias, A.; Bate, M. (Cell, 1987)
The expression of a subset of homologous genes of the AS-C is required during embryogenesis and metamorphosis for proper neural development. Here we study the expression of three of these genes (T3, T4, and T5) and show that their transcripts accumulate at the blastoderm stage in periodic patterns coincident with the dorsoventral extent of the neuroectoderm. Subsequent expression is in partially overlapping patterns that correlate with the segregation of neuroblasts. These genes are not transcribed in neurons. We also show that a deficiency for the AS-C prevents the appearance of at least one identified class of neuroblasts. We propose that the AS-C is part of a network of genes responsible for the segregation of neuroblasts.